Submerged Machining of Steel and Aluminum - Saadieh, Abdel Salam (Eastern Mediterranean University EMU, 2015)
Machining is the process of removing material in the form of chips. It is the most widely used technique in manufacturing. It especially comes into play when specific dimensions and surface properties are required. One of the most important forms of machining is milling. This procedure can take place in either dry or submerged environment. Many parameters can be controlled during milling, and they affect the quality of the obtained surface. This study considers milling in a submerged environment. The cutting fluid used is useful in reducing friction and heat generated during the process. Two types of materials are used for work-pieces: Steel CK45, and Aluminum Al6015. The study investigates the effect of five parameters on the roughness and hardness of the machined surface. These parameters are depth of cut, spindle speed, feed rate, tool size, and number of cuts. The effect of each parameter alone is studied by conducting a series of experiments where one parameter is varied while the remaining four are kept constant. Many researchers conducted studies about this topic in order to optimize the cutting parameters and obtain the best surface properties. Other studies focused on creating models that predict the surface roughness for a given set of parameters. In this study, it was found that a smaller depth of cut is better for the surface roughness (a value of 0.4 mm is recommended for both steel and aluminum). The feed rate is also recommended to be kept at a smaller value because a higher feed rate leads to a larger cutting force and more surface roughness. This is specially iv significant for aluminum. The optimal value for the feed rate was found to be 1000 mm/min. For better surface quality, the high spindle speed is required, and low speeds are not to be used in order to avoid failure in the milling. In these experiments, failure occurred at a speed of 1000 rpm while the best roughness was achieved at 4000 rpm for both materials. Fewer cuts are encouraged since they consume less time and produce better surface roughness. Specifically, two cuts lead to the best surface quality in both steel and aluminum. Finally, smaller cutting tools are advised for lower roughness values. The best to use is a small size tool while the large one caused failure due to the formation of large irregular chips. For steel, the combination that yielded the lowest roughness value was speed = 4000 rpm, feed rate = 1000 mm/m, depth of cut = 0.6 mm, number of cuts = 1, tool size = 12 mm. For this combination, Ra = 0.5 μm. As for aluminum, the combination that yielded the lowest roughness value was speed = 4000 rpm, feed rate = 1000 mm/m, depth of cut = 0.6 mm, number of cuts = 2, tool size = 50 mm. For this combination, Ra = 0.3 μm. Keywords: Chips, Milling, Submerged, Friction, Heat, Steel, Aluminum, Roughness, Hardness, Feed rate, Depth of cut, Speed, Number of cuts, Tool diameter, CK45, Al6015.

ÖZ: Makine isleminde parcanin cips şeklinde uzerinden alınması işlemidir.uretim alaninda en cok kullanilan islemdir.bu islem ozellikleolculendirilmesi hassas olan ve yuzey ozellikleri gerekmekte olan parcalar icin kullanilir.En onemli makina islemlerinden birisi frezedir.Bu islem hem kuru yuzeyde hemde sulu yuzeyde yapilabilir.Bu islem boyunca bircok sey kontrol edilebilir ve kaliteli yuzeyler elde edilir. Bu islem frezenin su icinde yapilmasini arastiriyor.Kesme sivisi surtunmeyi azaltmak icin faydali ve uretilen maddenin daha fazla isinmamasini saglar.Parcalar iki tip malzemeden olusmaktadir.celik CK45 ve aliminyum AL6015.Bu calisma bes tane etkenin uzerine arastirilmistir.Bunlar kesme bicagin donme hizi, ilerleme hizi,bicak olcusu ve kesme sayisi.Her etkenin tesiri arastirilmasi; bazi deneyler yapilarken parametlerden birisi degisitirilmis diger dordu sabit kalmistir.Arastirmacılar optımum kesım parametrelerını bulmak ıcın ve en iyi yuzey özelliklerini elde etmek için arastırmalar yapmıslardır. Genel olarak diğer çalışmalar parçaların yüzey pürüssüzlüğü üzerine yapılmıştır.Parametlerin etkisine odaklanılmıştır. Bu çalışmada, küçük kesme derinlikleri daha iyi yüzey pürüssüzlüğünü elde etme yöntemleri bulunmaktadır. İlerleme hızının küçük olması önerilmektedir.Çünkü yüksek ilerleme hızları daha fazla kesme gücüne ve daha kötü yüzey elde etmemize sebep olur.Bu özellikle aliminyum için önemlidir.İlerleme hızı için optimum değer 1000mm/dk.Daha iyi yüzey kalitesi için yüksek kesme hızı gereklidir ayrıca düşük hızda frezede hataları azaltmak için kullanılmamaktadır.Bu deneyde hataların vi genelde 1000rpm hızda en iyi yüzeyin ise 4000rpm’de olduğu iki farklı parçada deneyler test edilmiştir.Az kesimle üretilen parçalara daha az zaman harcanılmış ve daha iyi yüzsey pürüssüzlüğü elde edilmiştir.Özellikle iki defa kesilen parçalarda en iyi yüzey pürüssüzlüğü elde edilmiştir.Bu parçalar aliminyum ve çeliktir.Düşük yüzey kalitesi elde etmek için küçük kesme bıcaçları kullanılmaktadır.Küçük boyutlu bıçaklar, büyük boyutlu bıçaklara göre daha kullanışlıdır çünkü büyük boyutlu bıcaklar daha büyük çapakları oluşturuyor buda daha büyük hatalara sebebiyet veriyor. Çelik için en düşük pürüssüzlük değeri elde etmek için bu kombinasyon gerekmektedir; 4000rpm, ilerleme hızı 1000rpm kesme derinliği 0.6mm, kesim sayısı 1, bıçak büyüklüğü 12mm.Bu kombinasyon bize Ra=0.5μm verir. Aluminyum için en düşük pürüssüzlük değeri elde etmek için bu kombinasyon gerekmektedir.Hız 4000rpm, ilerleme hızı 1000rpm, kesme derinliği 0.6mm, kesim sayısı 2, bıçak büyüklüğü 50mm.Ra=0.3μm. Anahtar Kelemeler: cips, frez, su icinde, sürtünme, isi, celik, aluminyum, purusuzluk, sertlik,kesme hizi, kesme derinligi, hiz, kesme sayisi, bicak olcumu, CK45, AL6015.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2015. Co-Supervisor: Assist. Prof. Dr. Tahir Abdul Hussain, Supervisor: Assist. Prof. Dr. Ghulam Hussain.
Keywords: Mechanical Engineering; Machining; Chips; Milling; Submerged; Friction; Heat; Steel; Aluminum; Roughness; Hardness; Feed rate; Depth of cut; Speed; Number of cuts; Tool diameter; CK45; Al6015